2004
DOI: 10.1055/s-2004-814524
|View full text |Cite
|
Sign up to set email alerts
|

Different Mixtures of Sodium Hyaluronate and Their Ability to Create Submucosal Fluid Cushions for Endoscopic Mucosal Resection

Abstract: A mixture of higher molecular weight sodium hyaluronate with a sugar solution (particularly 20 % dextrose), with or without glycerin, should be regarded as a cost-effective option for creating SFCs instead of the conventional SH solution made with the same amount of a 1 % 800 kDa SH preparation and normal saline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(82 citation statements)
references
References 9 publications
1
79
1
1
Order By: Relevance
“…It was reported that a hyaluronic acid solution makes a better long-lasting submucosal cushion without tissue damage than other available solutions [7,[20][21][22][23] . As a further improvement of hyaluronic acid solution, usefulness of a mixture of high-molecular-weight hyaluronic acid, glycerin, and sugar has also been reported [24,25] . ESD is characterized by three steps: injecting fluid into the submucosa to elevate the lesion from the muscle layer, circumferential cutting of the surrounding mucosa of the lesion, and subsequent dissection of the connective tissue of the submucosa beneath the lesion.…”
Section: Development Of Esdmentioning
confidence: 99%
“…It was reported that a hyaluronic acid solution makes a better long-lasting submucosal cushion without tissue damage than other available solutions [7,[20][21][22][23] . As a further improvement of hyaluronic acid solution, usefulness of a mixture of high-molecular-weight hyaluronic acid, glycerin, and sugar has also been reported [24,25] . ESD is characterized by three steps: injecting fluid into the submucosa to elevate the lesion from the muscle layer, circumferential cutting of the surrounding mucosa of the lesion, and subsequent dissection of the connective tissue of the submucosa beneath the lesion.…”
Section: Development Of Esdmentioning
confidence: 99%
“…Besides that, SH is a synthetic product that could potentially cause antigenic reactions (4) . HPMC has been identified as an economical alternative to SH, being similarly effective at a dramatically lower cost, with no storage requirement, no need for reconstitution before use and minimal tissue reaction (3) .…”
Section: Recently Various Emr Devices Have Been V 47 -No2 -Abr/jumentioning
confidence: 99%
“…One of the major complications of EMR is perforation (15,16) . The most effective method of preventing perforation is to create an adequate submucosal fluid cushion (SFC) between the lesion and the muscle layer by submucosal injection (4) . A SFC lifts the mucosa around the target lesion facilitating resection techniques and protecting from deeper tissue injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that a hyaluronic acid solution makes a better long-lasting submucosal cushion without tissue damage than other available solutions [29][30][31][32][33] . As a further improvement of hyaluronic acid solution, usefulness of a mixture of high-molecularweight hyaluronic acid, glycerin, and sugar has also been reported [34,35] . A representative case of ESD procedure using a flex-knife and a mixture of high-molecular-weight hyaluronic acid, glycerin, and sugar is shown in Figure 2 [36] .…”
Section: Cosal Dissectionmentioning
confidence: 99%